THE ROLE OF FRONTAGE BUILDING TOWARDS ESTABLISHMENT OF PEDESTRIAN AREA IN JL. JENDERAL SUDIRMAN - K. (Jurnal Riset Arsitektur, 2019)
Abstract- In the early stage of the scenario realization has been done improvements in the alun alun area, also Jl. Jend. Sudirman. In the year 2016 carried out revitalization pedestrian paths on block Jl. Jend. Sudirman. Revitalization of pedestrian paths is preferred because pedestrian paths are the most basic public spaces to facilitate the movement of pedestrians from one place to another. However, the activity on this relatively new pedestrian path affects other names with existing building frontages.By qualitative method, this research read the pattern of dissemination of activity and condition of frontage of building on research object. This is done to determine whether the frontage of buildings and activities in the outer space have a relationship with each other. From this study found that the activity is not only influenced by the nature and material frontage of the building, but there is also a typology of space formed by the frontage of the building. Typology of space is closely related to the activities that occur in outer space.                 Key Words: Frontage, Active Frontage, City Furniture, Building Functions, Activities, Outer Space.